Comparative Analysis of Rrs486 and Rrs551 Wavelength Effectiveness from SNPP_VIIRS Satellite Imagery for Chlorophyll-a Mapping in Madura Strait, East Java - Apriliana, Diyah Ayu; Yuliano, Hendrikus; Wibisana, Hendrata (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
This study assesses the comparative performance of two remote sensing reflectance (Rrs) wavelengths, Rrs486 and Rrs551, derived from Suomi NPP VIIRS imagery, for estimating chlorophyll-a (chl-a) concentration in the Madura Strait, East Java, Indonesia. SNPP-VIIRS data from January 2025 and in-situ chl-a measurements from 25 sampling stations were analyzed to evaluate statistical relationships between satellite-derived Rrs and field observations. Correlation results show that Rrs486 has a stronger negative relationship with chl-a (r = –0.92) than Rrs551 (r = –0.83). Empirical algorithms developed for each wavelength indicate superior performance of the Rrs486-based model, yielding R² = 0.84, RMSE = 0.0021 mg/m³, and MAPE = 6.8%. In comparison, the Rrs551-based model produced lower accuracy with R² = 0.69, RMSE = 0.0037 mg/m³, and MAPE = 11.2%. A reflectance ratio algorithm (Rrs486/Rrs551) also demonstrated strong predictive potential (R² = 0.88). Spatial mapping using the optimal Rrs486 algorithm revealed higher chl-a concentrations near coastal zones and lower values in offshore waters. Overall, the findings confirm that Rrs486 provides more reliable chl-a estimations due to its spectral proximity to chlorophyll-a absorption features, supporting improved satellite-based monitoring in tropical coastal environments.